Energy consumption and costs of heating a detached house with wood briquettes in comparison to other fuels. (1st August 2016) - Stolarski, Mariusz Jerzy; Krzyżaniak, Michał; Warmiński, Kazimierz; Niksa, Dariusz
Highlights: Consumption of energy for heating with wood briquettes was from 121 to 130 GJ/year. Consumption of heat ranged from 0.40 to 0.42 GJ/m 2 /year. Cost of heat production from wood briquettes ranged from €772 to €986. Cost of 1 GJ of heat from wood briquettes decreased in the last heating season. Using other fuels increased cost of heating compared to wood briquettes by 12–235%. Abstract: This paper presents the consumption of energy needed to heat a detached house located in the north-east of Poland, as well as the cost of heat generation by combustion of wood briquettes compared to other biomass fuels and fossil fuels. The annual average consumption of briquettes during three heating seasons was 6.93–7.42 t/year and the annual consumption of fuel energy was 121–130 GJ/year. Expressed as energy per unit area of the house, the consumption of heat ranged from 0.40 to 0.42 GJ/m 2 /year. The average annual consumption of heat per person was 20.22–21.65 GJ. The annual cost of production of heat from briquettes for a house ranged from €772 to €986 during the three seasons under study. The cost of energy production from this fuel was much lower compared to fuel oil, natural gas, coal and pellets, but was higher compared to willow chips. Briquettes, which are produced in Poland in piston briquetting presses and which can be used as fuel in automatic boilers, is a prospective and promising feedstock for generating heat for family houses. The high price of new automatic biomass boilers is the main barrier in the modernisation of boiler houses.